Advances in X-Ray Analysis 1978
DOI: 10.1007/978-1-4613-9984-1_7
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Fluorescence Capabilities for Uranium Ore Analysis

Abstract: A rapid x-ray fluorescence (XRF) method for the quantitative analysis of uranium i n ore and process samples i s demonstrated. The method requires no uranium ore standar.ds and provides a relative precision of 22.5%. Particl e-size and sel f-absorption effects are eval uated a1 ong wi t h current methods of exci t a t i on and detection for M, L, and K series uranium x-rays. Sensitivities and detection 1 imi t s are comparable using either energy dispersive or wavelength dispersive analysis of uranium L x-rays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Poor temperature here can alter the consistency and acidity of product. Nielson (1974) has indicated that variation of cooling after incubation can alter the viscosity of yoghurt, and its stability against syneresis. Puchan, Banhegyi & Flueler (1974) have shown that the activity of micro-organisms and consequently the acidity of yoghurt was markedly affected by storage temperatures.…”
Section: Yoghurtmentioning
confidence: 99%
“…Poor temperature here can alter the consistency and acidity of product. Nielson (1974) has indicated that variation of cooling after incubation can alter the viscosity of yoghurt, and its stability against syneresis. Puchan, Banhegyi & Flueler (1974) have shown that the activity of micro-organisms and consequently the acidity of yoghurt was markedly affected by storage temperatures.…”
Section: Yoghurtmentioning
confidence: 99%